The aims of business management - Nikolaos Papavassiliou (Intereconomics, 1975)
International joint ventures are progressively growing more important in LDCs. However, their activvities frequently lead to conflicts between such countries' overall economic objectives and the aims of business management.
Keywords: 330; Joint Ventures